Quality Indicators for Colonoscopy and the Risk of Interval Cancer - Kaminski, Michal F; Regula, Jaroslaw; Kraszewska, Ewa; Polkowski, Marcin; Wojciechowska, Urszula; Didkowska, Joanna; Zwierko, Maria; Rupinski, Maciej; Nowacki, Marek P; Butruk, Eugeniusz (The New England journal of medicine, 2010)
In this large study of colorectal-cancer screening, the endoscopist's rate of adenoma detection was associated with the risk of interval colorectal cancer after screening colonoscopy. Colorectal cancers were less likely to be diagnosed between screening examinations when colonoscopies were performed by endoscopists with an adenoma detection rate of 20% or more. In this large study of colorectal-cancer screening, the endoscopist's rate of adenoma detection was associated with the risk of interval colorectal cancer after screening colonoscopy. Although colonoscopy is widely used for colorectal-cancer screening, 1 – 3 its miss rate for cancers and adenomatous polyps (benign premalignant tumors or adenomas), which is low but not negligible, remains a concern. 4 – 6 It has been suggested that a high-quality examination that ensures the detection and removal of all neoplastic lesions is key for screening efficacy. 6 – 8 In response, professional societies have proposed the use of various quality-assessment indicators. Of such indicators, the rates of adenoma detection and cecal intubation are the most commonly used. 7 – 10 However, these measurements have never been validated, and it is not known whether an improvement . . .